2007
DOI: 10.1073/pnas.0706847104
|View full text |Cite
|
Sign up to set email alerts
|

Polyphosphate kinase 1, a conserved bacterial enzyme, in a eukaryote, Dictyostelium discoideum , with a role in cytokinesis

Abstract: Polyphosphate kinase 1 (PPK1), the principal enzyme responsible for reversible synthesis of polyphosphate (poly P) from the terminal phosphate of ATP, is highly conserved in bacteria and archaea. Dictyostelium discoideum, a social slime mold, is one of a few eukaryotes known to possess a PPK1 homolog (DdPPK1). Compared with PPK1 of Escherichia coli, DdPPK1 contains the conserved residues for ATP binding and autophosphorylation, but has an N-terminal extension of 370 aa, lacking homology with any known protein.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
51
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 31 publications
1
51
0
Order By: Relevance
“…The characterization of two D. discoideum enzymes Ppk1 (20) and DdPPK2 (22) able to synthesize polyP in vitro suggested that both enzymes might contribute to the synthesis of polyP in vivo. DdPPK2 has been identified as an actin-related protein complex but the specific gene was not cloned.…”
Section: Ppk1 the Only Enzyme Responsible For Polyp Synthesis Controlmentioning
confidence: 99%
See 3 more Smart Citations
“…The characterization of two D. discoideum enzymes Ppk1 (20) and DdPPK2 (22) able to synthesize polyP in vitro suggested that both enzymes might contribute to the synthesis of polyP in vivo. DdPPK2 has been identified as an actin-related protein complex but the specific gene was not cloned.…”
Section: Ppk1 the Only Enzyme Responsible For Polyp Synthesis Controlmentioning
confidence: 99%
“…The first, DdPPK1 (hereafter refer as Ppk1), was identified by homology to the bacterial polyphosphate kinase (PPK) sequence (20). Dictyostelids represent the only eukaryote class possessing a bacterial-like PPK, suggesting the gene was obtained by a horizontal gene transfer event (20). The second protein complex, named DdPPK2, was identified after biochemical purification of polyphosphate kinase activity and was found to comprise one actin-related protein and two actin-associated proteins (21).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Transcriptome analysis of Campylobacter jejuni polyphosphate kinase (ppk1 and ppk2) mutants the synthesis of poly-P, [11][12][13] while PPK2 preferentially facilitates the generation of GTP from poly-P. [14][15] Both PPK1 and PPK2 (PPKs) contribute to survival, adaptation, and virulence in many bacterial pathogens. 11 For example, we have shown that the impairment of the ppks (ppk1 and ppk2) can affect a wide range of phenotypes in C. jejuni, [4][5][6] including biofilm formation, and the resistance to osmotic, nutrient, and antimicrobial stresses.…”
mentioning
confidence: 99%